Mathematics belief impact on metacognition in solving geometry: Middle school students - Suliani, Mega; Juniati, Dwi; Lukito, Agung (Intelektual Pustaka Media Utama, 2024)
Mathematical beliefs and metacognitive knowledge play significant roles in solving mathematical problems; thus, this study aims to investigate the influence of middle school students' beliefs on their metacognitive knowledge when solving geometry problems. This study utilizes both quantitative and qualitative research methods. A linear regression test was used to determine the effect of middle school students' beliefs on their metacognitive knowledge. The results of the quantitative research analysis were followed up with a qualitative research approach to describe the metacognitive knowledge of students who have high and low confidence in solving geometric problems. This research involved 352 middle school students in the Tarakan area. Based on the results of linear regression, it is known that the beliefs of middle school students have a positive effect on their metacognitive knowledge when solving geometric problems. In addition, it was found that students with different beliefs could solve a given geometry problem, but the approach to solving it varied among subjects. Middle school students have diverse beliefs, but these variations do not affect their capacity to apply their metacognitive knowledge at every stage of solving mathematical problems.